Baskets and Architecture: Ritualistic Making and Collective Design. (July 2017) - Aranda, Benjamin; Lasch, Chris
Abstract : Is algorithmic design and fabrication really a new thing? Not according to Benjamin Aranda and Chris Lasch, co‐founders of New York and Tucson‐based design studio Aranda\Lasch. Through over a decade of collaborations with a Native American basket weaver, they have observed clear parallels between age‐old craft forms and contemporary architectural processes. Here they give their account of the outcomes of these collaborations to date, including an ongoing project for sophisticated collective construction to serve indigenous communities.